2015
DOI: 10.1073/pnas.1421675112
|View full text |Cite
|
Sign up to set email alerts
|

21st century United States emissions mitigation could increase water stress more than the climate change it is mitigating

Abstract: There is evidence that warming leads to greater evapotranspiration and surface drying, thus contributing to increasing intensity and duration of drought and implying that mitigation would reduce water stresses. However, understanding the overall impact of climate change mitigation on water resources requires accounting for the second part of the equation, i.e., the impact of mitigationinduced changes in water demands from human activities. By using integrated, high-resolution models of human and natural system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
131
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 41 publications
4
131
1
Order By: Relevance
“…In addition, the energy sector itself requires considerable water resources (Bijl et al, 2016). Fossil fuel extraction such as coal mining and shale gas fracking are highly water intensive, whilst biofuel production competes with food production for land and water resources (Bonsch et al, 2016;Hejazi et al, 2015). Failure to capture sectoral interdependencies means we may fail to identify synergistic solutions; or worse still, policies in one sector may have unintended negative consequences in another.…”
Section: Sectoral Interdependencementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the energy sector itself requires considerable water resources (Bijl et al, 2016). Fossil fuel extraction such as coal mining and shale gas fracking are highly water intensive, whilst biofuel production competes with food production for land and water resources (Bonsch et al, 2016;Hejazi et al, 2015). Failure to capture sectoral interdependencies means we may fail to identify synergistic solutions; or worse still, policies in one sector may have unintended negative consequences in another.…”
Section: Sectoral Interdependencementioning
confidence: 99%
“…An integrated approach has also been applied by Bonsch et al (2016) using MAgPIE (Lotze-Campen et al, 2008, a global land and water use allocation model, to understand the trade-off between agricultural expansion and intensification via water abstraction to meet biofuel targets. Like Hejazi et al (2015), their integrated approach showed that changes in the energy sector can lead to competition for water resources within the food sector. The MAgPIE approach also underlined the importance of capturing dynamic vegetation and hydrological processes in the same modelling framework as the two are intrinsically intertwined, with changes in vegetation impacting water resources and vice versa Konar et al, 2013;Lotze-Campen et al, 2008).…”
Section: Sectoral Interdependencementioning
confidence: 99%
See 1 more Smart Citation
“…235 water basins [21]). GCAM is often used as a boundary condition and coupled to sectoral models, such as the Community Land Model and Xanthos, which typically operate at finer spatial and temporal scales than GCAM [19,20]. For example, Xanthos is a globally gridded hydrology model that operates at monthly scale.…”
Section: Introductionmentioning
confidence: 99%
“…3. Electricity: Temporal downscaling of electricity water withdrawal from annual to monthly was based on the assumption that the amount of water withdrawal for electricity generation is proportional to the amount of electricity generated [19,20]. 4.…”
Section: Introductionmentioning
confidence: 99%